ANALYSIS BETWEEN ANIMATED VIDEO AND DENTAL PHANTOM IN TOOTH BRUSHING EDUCATION - I Ketut Harapan; Jeineke E. Ratuela; Salikun Salikun; Anneke A. Tahulending (Jurnal Riset Kesehatan, 2022)
Dental caries have been a problem in childhood. Poor knowledge causes poor dental hygiene. Health promotion is urged to conduct to give children of school age an understanding of how important is dental hygiene. Tooth brushing is a way to prevent dental caries. We initiated tooth brushing education research with a quasi-experimental design with a two-group pre-posttest design. The sample was taken with purposive sampling with 66 students in SDN Kalase, SDN Butong, and SDN Tateli located in a working area of Tateli Public Health Service, Minahasa, North Sulawesi, Indonesia. We employed animated video and dental phantom as the media and compare their effectiveness. First, we performed a normality test, the data is found not normally distributed. Hence, the Wilcoxon test was used to analyze whether the difference in the data exists, and the Mann-Whitney test was conducted to know whether the difference is significant. From the mean value of the Mann-Whitney test results, the effective of the methods is obtained. The results show that the Mann-Whitney test obtained Asymp. Sig (2 tailed) value of 0.000, less than a probability value of 0.005. Thus, there is a significant difference in knowledge level increase. The result of Mean value of a group with animated video is 49.26, higher than the dental phantom media group with only 17.74. So, in conclusion, animated video media is more effective than dental phantom media in improving students' knowledge level of tooth brushing.